2013
DOI: 10.1111/imre.12014
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Employment Success in Canada: Examining the Rate of Obtaining a Job Match

Abstract: This study employs longitudinal data to examine the rate at which recent immigrants to Canada obtain employment matching their previous or intended occupations. Socio-demographic factors such as visible minority status and area of residence are found to influence the rate at which this cohort of immigrants obtains job matches. Human capital factors also have a significant impact. An examination of occupational characteristics reveals that immigrants who seek high-status occupations obtain job matches at slower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 35 publications
0
44
1
1
Order By: Relevance
“…As a consequence, they have higher poverty rates (Kazemipur and Halli ; Picot, Hou, and Coulombe ; Picot, Lu, and Hou ). All too often, highly skilled immigrants experience profound occupational degradation (Krahn et al., ; Frank ). When immigrants do find work in their field, they earn considerably less than similar workers who were born in Canada (Hum and Simpson ).…”
Section: The Context Of Recent Immigration To Canadamentioning
confidence: 99%
“…As a consequence, they have higher poverty rates (Kazemipur and Halli ; Picot, Hou, and Coulombe ; Picot, Lu, and Hou ). All too often, highly skilled immigrants experience profound occupational degradation (Krahn et al., ; Frank ). When immigrants do find work in their field, they earn considerably less than similar workers who were born in Canada (Hum and Simpson ).…”
Section: The Context Of Recent Immigration To Canadamentioning
confidence: 99%
“…Research evidence suggests that across Western migrant societies, race and birthplace origins can have an effect on whether or not some groups will experience upward socioeconomic mobility (Bauder, 2003;Frank, 2013;Valtonen, 2001;Weedon, 2002). This has been shown to be the case for 'non-white' ethnic minorities who, despite having very high levels of education, are particularly vulnerable to social exclusion.…”
Section: Citizenship and Social Inclusionmentioning
confidence: 99%
“…Notwithstanding the differences in terminologies and definitions of various types of international workers, and differences in newcomers' countries of origin, there is an important commonality in that newcomers need to find employment (with the exception of traditional expatriates who typically have jobs prior to migrating) to fully function and integrate in the country of destination (Cerdin et al, 2014;Crowley-Henry et al, 2016;Dietz et al, 2015;Fang et al, 2013;Frank, 2013;Guo and Al Ariss, 2015;Reitz, 2007a, 200b;Reitz et al, 2014). Integration of newcomers in the local labour market is critical for their successful settlement and adjustment, and overall wellbeing (Dietz et al, 2015;Hansen, 2012;Khoir et al, 2015b;Mahajan and Toh, 2014;Paul and Moser, 2009;Reitz et al, 2014;Wang and Sangalang, 2005).…”
Section: Labour Market Integration Of Newcomersmentioning
confidence: 99%
“…It is well established that newcomers need to find suitable employment to fully function in the new country (Dietz et al, 2015;Fang et al, 2013;Frank, 2013;Frijters et al, 2005;Reitz, 2001;Reitz et al, 2014;Wang and Sangalang, 2005). Research has shown that integration of newcomers in the new country's labour market is critical for their settlement, adjustment and integration in the receiving society, culture and environment (Bevelander and Pendakur, 2014;Caidi et al, 2010;Frank, 2013;Hansen, 2012;Lundborg, 2013;Reitz, 2007aReitz, , 2007bSambasivan et al, 2017;Singh and Mahmood, 2017;Wang and Sangalang, 2005). Employment grants newcomers a sense of belonging, recognition, and acceptance in the new society (Dietz et al, 2015;Frank, 2013;Hansen, 2012;Reitz et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation